2018
DOI: 10.1016/s2095-3119(17)61837-9
|View full text |Cite
|
Sign up to set email alerts
|

Improve access to the EU market by identifying French consumer preference for fresh fruit from China

Abstract: Most previous studies have investigated country-of-origin effect for agricultural products from the economically developed country, but few have focused on the impact of country-of-origin on agricultural products from economically developing countries. Using a national online survey in France, we determine French consumers' perceptions and preferences for fresh fruit from China. Results of ordered logit models show that fresh fruit from China was perceived as low quality and unsafe. Respondents who care about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In contrast, imported apples have an advantage on the attributes of price, taste, size, color, skin condition, and promotion. For research on the preference of local apples is carried out by [16] and preference for fresh fruit from China [17]. The study also measured consumers' attitudes towards fruits based on evaluation or consumer attitudes towards some of the attributes of fruits and vegetables studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, imported apples have an advantage on the attributes of price, taste, size, color, skin condition, and promotion. For research on the preference of local apples is carried out by [16] and preference for fresh fruit from China [17]. The study also measured consumers' attitudes towards fruits based on evaluation or consumer attitudes towards some of the attributes of fruits and vegetables studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there exist numerous previous studies of consumer behavior in normal circumstances (Wang et al 2018 ; Gao et al 2019 ), no such studies exist about consumer stockpiling behavior and preferences in emergencies. Consumer behavior and preference are quite special and different from the common scenario (Kurihara et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fast development of the Chinese food industry has been accompanied by frequent food safety incidents [ 1 , 2 ] that have undermined consumer trust in food safety [ 3 , 4 , 5 , 6 ] and have limited the international reputation of the Chinese food industry [ 7 , 8 , 9 , 10 , 11 , 12 ]. Many studies reported weaknesses in China’s food safety system, which are mainly related to poor law enforcement and inefficient supervision of governmental agencies [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%